Volatility Spillover of Brent Oil Price Return on Return of Iran and USA Financial Markets and Related Industries: A MGARCH Approach - Reza Tehrani (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2017)
The importance of oil price volatility spillover has significantly increased since the globalization and financial markets’ interaction have expanded. Based on this, the oil price impact on financial markets, as an exogenous variable, is also increased. In this paper, we study the “volatility spillover of Brent oil price return effects on return of Iran and USA financial markets during 2008-2016 using weekly data. Results show that volatility of Brent oil price return spillovers S&P500 and related industries to oil indexes in USA, so it does not spillover Tehran exchange price index return and related industries to oil indexes in Iran. Also financial market indexes return do not spillover together in short-time.